Changes in Mortality Patterns Following Total Hip or Knee Arthroplasty Over the Past Two Decades: A Nationwide Cohort Study. Issue 2 (February 2014) - Lalmohamed, Arief; Vestergaard, Peter; de Boer, Anthonius; Leufkens, Hubertus G. M.; van Staa, Tjeerd P.; de Vries, Frank
<x xml:space="preserve">Abstract</x> Objective Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are effective procedures for patients with moderate‐to‐severe osteoarthritis. Mortality rates after THA and TKA may have changed because of new surgical techniques, improvement of peri‐ and postoperative care, and performance of surgery in older patients having multiple comorbidities. However, data on secular mortality trends are scarce. We undertook this study to evaluate mortality patterns between 1989 and 2007 in patients undergoing elective THA and TKA. Methods In a Danish retrospective nationwide cohort study, 71, 812 patients who underwent THA and 40, 642 patients who underwent TKA were identified between January 1989 and December 2007. All‐cause and disease‐specific mortality was assessed, stratified by calendar periods. Using Cox proportional hazards models, relative risks (RRs) of mortality were calculated between different calendar periods, adjusted for age, sex, and comorbid diseases. Results Since the early 1990s, short‐term survival following elective THA and TKA has greatly improved. Compared with the period between 1989 and 1991, 60‐day mortality rates between 2004 and 2007 were substantially lower for patients undergoing THA (RR 0.40, 95% confidence interval [95% CI] 0.28–0.58) and for patients undergoing TKA (RR 0.37, 95% CI 0.21–0.67). This trend was far superior to what was seen in the general population. The decrease in mortality was greatest for deaths from myocardial infarction, venous thromboembolism, pneumonia, and stroke. Patients tended to have more presurgical comorbidity over time, and the duration of hospital stay was roughly halved. Conclusion Mortality rates following elective THA and TKA have decreased substantially since the early 1990s, despite patients having more presurgical comorbidity. These findings are reassuring for patients undergoing elective THA or TKA.